A divulgação científica a partir das atividades de experimentação junto a alunos do ensino fundamental II - Almeida, Elder Tanio Gomes de (2018)
Considering that the Scientific Divulgation in the school scope needs to be presented as a relevant part of the teaching to the understanding of the phenomena that are present in the daily life of the students. It is problematic how the scientific dissemination from the experimental activities constituted as a significant strategy for the students of the 9th grade. Therefore, the research was carried out in the Municipal School Professor Edinir Telles Guimarães located in the eastern part of the city of Manaus by the qualitative approach, started with two questions in 2016 and an interview in 2017 about the scientific dissemination with the experimentation. For the interpretation of the data used the discursive textual analysis-DTA. It was possible to observe that Scientific Dissemination with experimentation provides the students' interest in natural phenomena as a significant strategy in science teaching, which allows to conclude that the practical activities contribute with discussions on scientific subjects Keywords: Scientific divulgation. Experimentation. Elementary School. Natural Phenomena